The Effect Of Digital Leadership Style and Collaborative Culture on Employee Performance with Teamwork as a Intervening Variables at PT PLN (Persero) UP2K Sumut) - Ahmed Maulana; Hernawaty (Equivalent : Journal of Economic, Accounting and Management, 2026)
The purpose of this research is to investigate how Collaborative Culture and Digital Leadership Style impact Employee Performance, with Teamwork acting as a mediating factor. A total of 78 employees participated in this study. Data was gathered via questionnaires and examined using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of the analysis show that both Collaborative Culture and Digital Leadership Style positively and significantly influence Employee Performance. Additionally, Digital Leadership Style positively and significantly affects Teamwork. On the other hand, Teamwork does not directly affect Employee Performance significantly and does not mediate the effects of Collaborative Culture or Digital Leadership Style on Employee Performance. These results suggest that enhancing a collaborative culture and practicing effective digital leadership are essential for boosting employee performance.